Effect of Chinese herbal compounds on ocular fundus signs and vision in conventional treated-persons with non-proliferative diabetic retinopathy: A systematic review and meta-analysis - Xiaodong Li; Jiaqi Zhang; Runxi He; Xiaojuan Su; Zhilin Li; Xuejun Xie (Frontiers in Endocrinology, 2022)
BackgroundChanges in fundus signs and loss of visual acuity are an important basis for screening and treating diabetic patients with retinopathy, and conventional Western medicine is moderately effective in treating diabetic retinopathy(DR),To systematically evaluate the effectiveness and safety of Chinese herbal compounds(CHCs) in the combined treatment of diabetic retinopathy.MethodSix electronic databases, including PubMed, were searched to screen eligible literature. Randomized controlled trials of non-proliferative diabetic retinopathy(NPDR) were included, in which the control group was treated with conventional Western-based drugs or retinal laser photocoagulation, and the intervention group was treated with CHCs in combination based on the control group.The Cochrane Risk of Bias Assessment Tool was used to evaluate the quality of the literature, and the RevMan 5.4 software was used for statistical analysis.ResultsCompared with Conventional group alone,CHCs group was superior at improving clinical efficacy [RR=1.29, 95%CI=(1.23, 1.36),P<0.01] and best corrected visual acuity(BCVA) [MD=0.10,95%CI=(0.09,0.12),P<0.01],it was also superior at reducing the number of microangiomas [MD=-2.37, 95%CI=(-3.26, -1.49),P<0.01], microangioma volume [MD=-4.72, 95%CI=(-5.14, -4.29), P<0.01], hemorrhagic spots [MD=-2.05, 95%CI=(-2.51,-1.59), P<0.01], hemorrhagic area [MD=-0.76, 95%CI=(-1.06, -0.47), P<0.01], hard exudates [MD= -1.86, 95%CI=(-2.43, -1.28), P<0.01], cotton lint spots [MD= -0.93, 95%CI= (-1.31, -0.55), P<0.01], central macular thickness(CMT) [SMD=-1.52, 95%CI=(-1.85, -1.19),P<0.01], Chinese medicine evidence score [SMD=-1.33,95%CI=(-1.58, -1.08),P<0.01], fasting blood glucose (FBG) [SMD=-0.47, 95%CI=(-0.61,-0.33),P<0.01], 2h postprandial blood glucose(2hPBG) [SMD=-0.87, 95% CI=(-1.06, -0.67), P<0.01], glycosylated hemoglobin (HbAlc) [SMD=-0.76, 95%CI=(-1.16, -0.3),P<0.01], total cholesterol(TC) [SMD=-0.33,95%CI=(-0.51,-0.16),P<0.01],and CHCs group with less adverse events occurred [RR=0.46, 95%CI=(0.29, 0.74),P<0.01].ConclusionCHCs combined with conventional medicine for NPDR has better clinical efficacy and higher safety, but the above findings need further validation in more large sample, multicenter, and low-bias RCTs due to the limitation of the quality and quantity of included literature.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42022342137.